2014
DOI: 10.7243/2055-091x-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D have protective effect on human nasal polyposis: histological and immunohistochemical study

Abstract: Background: Nasal polyps (NPs) are benign pedicled mucosal protrusions into the nasal cavity of multifactorial origin. Vitamin D has been demonstrated as having potential immunomodulatory activity and act as an antiproliferative agents. Aim of the work: To determine the possible antiproliferative effect and immunomodulatory activity of VD on human nasal polyposis. Material and methods: Based on thirty patients and divided equally into 3 groups. Group Ι (healthy subjects). Group ΙΙ were received low daily oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, it was concluded that high-dose VD 3 supplementation may be more effective in the clinical improvement, relief of NP symptoms, and postoperative nasal mucosa repair due to its anti-inflammatory role in the body. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was concluded that high-dose VD 3 supplementation may be more effective in the clinical improvement, relief of NP symptoms, and postoperative nasal mucosa repair due to its anti-inflammatory role in the body. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of VD at high therapeutic doses has been known to reduce the size of the NPs, relieve the symptoms of NPs, and restore nasal mucosa to its normal state. [ 16 17 18 ] Therefore, these findings may be useful in two ways, first to allow more effective types of NP treatment, especially in patients with poor conditions or in patients who refuse surgery, and secondly to prescribe VD as a posttreatment supplement after surgery to prevent NP recurrence. However, given the uncertainty in this area, further studies seem to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis result was in accord with a study by Faruk, which indicated that vitamin D is protective against the development of sinusitis and that the lack of vitamin D might induce the development of pre-septal cellulitis. Meanwhile the symptoms and signs of CRS could be relieved by administration of vitamin D. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Faruk et al [18] investigated the efficacy of a large -dose [4000 IU/day] and a low-dose [1000 IU/day] vitamin D3 in lowering the size of nasal polyps and alleviating illness symptoms. The group that got high-dose vitamin D3 demonstrated a considerable reduction in all visual analogue scale symptoms [VAS] and endoscopic scores, which was almost identical to the results of the current investigation.…”
Section: Discussionmentioning
confidence: 99%